Floodwater storage capacity of the Middle Daugava floodplain (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This study highlights the flood risk prevention services provided by the Middle Daugava river-floodplain system located downstream from Daugavpils City. Today, it acts as a principal storage area for floodwaters of the Daugava River during the spring floods, therefore diminishing the risk of flooding and related costs for urban municipalities like Jēkabpils and Pļaviņas located further downstream. Statistical analysis of hydrological data records of the Daugava River at Daugavpils and Jēkabpils during the top-10 flood events in 20th century are performed in order to quantify the largest daily discharge deficits between these two hydrological posts as well as to calculate the amount of floodwaters that could be intercepted by the entire floodplain area. The highest daily discharge deficit (2230 m3 s-1) is used to calculate additional water level heights for Jēkabpils town if the floodplain did not intercept the floodwaters at all. Therefore, reduction of annual flood risk level provided by the existing river-floodplain system of the Middle Daugava River could be assessed from hydrological perspective as well as from the Ecosystem Services Concept point of view.